Accelerated exploration of multi-principal element alloys for structural applications. (September 2015) - Senkov, O.N.; Miller, J.D.; Miracle, D.B.; Woodward, C.
Abstract: A strategy for accelerated discovery and exploration of multi-principal element alloys was developed and used to identify new alloys within a design window of desired microstructures and properties. As an example, the strategy was applied to analyze thousands of 3- 4-, 5- and 6-component alloys at equiatomic compositions of the alloying elements. Currently available thermodynamic databases were used to assess equilibrium phase diagrams for these alloys. The validity and reliability of the calculated phase diagrams were estimated based on the extent of experimental binary and ternary data used to build the respective thermodynamic databases. Alloys with specific characteristics, such as single-phase solid solution alloys with the use temperature above 1000 °C, were identified using an automated analysis of the calculated phase diagrams. The density, elastic moduli and costs of these alloys were estimated using the rule of mixtures of pure elements and were used as additional criteria for alloy selection. This approach allowed rapid, albeit preliminary, screening of many thousands of alloys and identification of promising candidate compositions, some of which are reported in this paper, for more time intensive experimental validations and assessments. Highlights: Multi-principal element alloys (MPEAs). CALPHAD was used for accelerated discovery and development of new MPEAs. Conditions for the formation of solid solution phases were analyzed. 157 new single-phase solid solution MPEAs were identified.